On the Relative Importance of Stratospheric and Tropospheric Drivers for the North Atlantic Jet Response to Sudden Stratospheric Warming Events - Gerstman Afargan, Hilla; id_orcid:0 000-0002-9169-2764; Jiménez Esteve, Bernat; id_orcid:0 000-0003-2706-5309; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X (American Meteorological Society, 2022)
ISSN:0894-8755 ISSN:1520-0442